Implementing Word Puzzle as Media for Teaching Vocabulary in SMP Muhammadiyah Pangsid - Nur Fathain; Buhari; Nurul Faradillah; Isumarni; Sam Hermansyah (INTERACTION: Jurnal Pendidikan Bahasa, 2026)
This study investigated the effectiveness of word puzzles as an innovative teaching medium in improving seventh-grade students’ vocabulary mastery at SMP Muhammadiyah Pangsid, Indonesia. The research was driven by the students’ persistently low vocabulary proficiency, which stemmed from conventional, teacher-centered methods that lacked engagement and failed to promote active learning. Employing a quantitative pre-experimental design with a one-group pretest-posttest approach, the study involved 21 seventh-grade students selected through total sampling. Vocabulary mastery was assessed using a 50-item test consisting of 10 multiple-choice items and 40 word puzzle items covering syllabus-based topics (animals, school objects, occupations, parts of the body, and daily activities). Data collected from pretest and posttest were analyzed using descriptive statistics and the Wilcoxon Signed-Rank Test, given the non-normal distribution of the data. The findings demonstrated a statistically significant improvement in students’ vocabulary mastery after the intervention. The mean score rose substantially from 16.33 in the pretest to 72.62 in the posttest. The Wilcoxon Signed-Rank Test produced a significance value of 0.001 (p < 0.05), leading to the rejection of the null hypothesis. These results confirm that word puzzles effectively enhance vocabulary acquisition by increasing student motivation, participation, and retention in an EFL context. The study recommends the integration of word puzzles as a practical, low-cost, and engaging alternative to traditional vocabulary instruction, particularly in junior high schools with limited resources.